Milo stover for growing heifers - Bolsen, K.K.; Boyett, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Five rations (involving 4 forage treatments) were compared: (1) forage sorghum silage, (2) forage sorghum silage ensiled with organic acids , (3) milo stover pellets, (4) milo stover silage and (5) milo stover silage plus rolled milo. Each ration was fed to 13 heifer calves for 114 days. No differences were observed in gain, intake or feed efficiency between heifers fed untreated and organic acid-treated forage sorghum silage. Pelleting milo stover increased dry matter consumption over milo stover silage but resulted in a poorer feed conversion. Adding rolled milo to stover silage improved gain and feed conversion compared to stover silage or pellets . Results indicate that growing heifers can make substantial winter gains on properly supplemented milo stover rations. The feeding value of forage sorghum silage was not improved by adding organic acids.
Keywords: Beef; Milo stover; Heifers; Silage